Congenital nasolacrimal duct mucocele–a case report - Brodkiewicz, Andrzej; Zakowska, Anna; Peregud-Pogorzelski, Jarosław; Gizewska, Maria; Burak, Mirosław; Pastuszak-Gabinowska, Magdalena (The Turkish Journal of Pediatrics, 2010)
Congenital nasolacrimal duct mucocele (CNDM) is a very rare condition in newborns. Prolapse or expansion of the mucocele into the nose may lead to respiratory distress and difficulty in feeding. The triad of cystic medial canthal mass, dilatation of the nasolacrimal duct and a contiguous sub-mucosal nasal mass on computed tomography (CT) is indicative in the diagnosis of CNDM. The case of a five-week-old girl with infected CNDM is described. The authors aim to emphasize the very rare incidence of CNDM in Polish newborns, delayed diagnosis in the case described and the paramount importance of CT of the head for the correct diagnosis and treatment.